2009
DOI: 10.1097/crd.0b013e3181b18e03
|View full text |Cite
|
Sign up to set email alerts
|

Essential Hypertension

Abstract: Inflammation is a key feature in the initiation, progression, and clinical implications of cardiovascular disorders, including essential hypertension. Increasing evidence shows that activation of renin-angiotensin-aldosterone system and enhanced local production of angiotensin II have been implicated in the pathophysiology of inflammation. Besides being a potent vasoactive peptide, angiotensin II regulates the inflammatory process. Specifically, it increases vascular permeability, participates in the recruitme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(21 citation statements)
references
References 85 publications
(77 reference statements)
1
14
2
Order By: Relevance
“…Angiotensin II acts not only as a vasopressor but also as a paracrine and autocrine hormone to promote cell growth, apoptosis, inflammation and tissue damage that ultimately lead to hypertrophy, fibrosis and heart failure (Paul et al 2006; Androulakis et al 2009). Studies have shown that mice with the Th2 phenotype are predisposed to heart disease (Huber&Lodge, 1986; Liao et al 1993; Afanasyeva et al 2001; Liao et al 2005), although their susceptibility to Ang II-induced cardiac damage (or lack of it) is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiotensin II acts not only as a vasopressor but also as a paracrine and autocrine hormone to promote cell growth, apoptosis, inflammation and tissue damage that ultimately lead to hypertrophy, fibrosis and heart failure (Paul et al 2006; Androulakis et al 2009). Studies have shown that mice with the Th2 phenotype are predisposed to heart disease (Huber&Lodge, 1986; Liao et al 1993; Afanasyeva et al 2001; Liao et al 2005), although their susceptibility to Ang II-induced cardiac damage (or lack of it) is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II (Ang II), a potent vasopressor, has been implicated in the inflammatory process (Suzuki et al 2003; Androulakis et al 2009). As Th1/Th2 imbalance plays a role in the pathophysiology of cardiovascular remodelling and dysfunction (Okura et al 1998; Shimizu et al 2004; Yu et al 2005; Yu et al 2006) and Balb/c mice are susceptible to heart disease (Huber & Lodge, 1986; Liao et al 1993), we hypothesized that in Ang II-induced hypertension the Th2-dominant Balb/c strain would develop exacerbated cardiac remodelling and impaired cardiac function, whereas the Th1-dominant C57BL/6 strain would be protected.…”
mentioning
confidence: 99%
“…Factors in the pathophysiology of hypertension noted by Page remain important and our knowledge of these individually are growing, for example, genetic, endocrine, and immune factors [5, 3438]. Of note, greater attention to renal involvement in hypertension has been combined with greater knowledge of the interaction of renal and neural control [39–43].…”
Section: Pathophysiology Of Essential Hypertensionmentioning
confidence: 99%
“…AngII also causes diapedesis (leukocyte extravasation) in inflammatory cells. It also increases the TGF-β signaling which is one of the main factors involved in the pathogenesis of cardiovascular disorders, including hypertension (18). Based on the findings of clinical and laboratory studies, other components of the RAS, including aldosterone and/or mineralocorticoid receptor (MR) can also lead to oxidative stress and vascular inflammation (19); as a consequence, the administration of aldosterone and MR stimulants increase the serum level of IL-6 and IL-12 (20).…”
Section: Introductionmentioning
confidence: 99%